Study the Effect of Using Different Bearing Types on the Performance of Evaporative Cooler - Hassan, Shaker S.; Shandookh, Ahmed Adnan; Ihsan, Omar Alaa (Al-Nahrain Journal for Engineering Sciences, 2018)
An investigation of performance response of two types of bearings such as Cylindrical Roller Bearing and bush bearing on evaporative cooler driven by DC motor of 1500 r.p.m, through studying many parameters like vibration response, temperature raise, humidity, sound level and total performance. high quality 3D positions X, Y and Z, vibration sensors type (ADXL335 accelerometers) with Arduino mega 2560 that interfaced with Lab-View program were used to measure changes in vibration amplitude and frequency. Two temperature sensors of type (LM35) were used to investigate the temperature raise in the bearings also with Arduino mega 2560 that interfaced with Lab-View program. For humidity a sensor of type DHT22 was used, also, a portable device was used to measure electricity consumption, rotary speed and sound level in the bearings of evaporative cooler. By replacing bearings all the parameters above wear measured then a comparison between them were made to find the best performance and operation of these bearings. The obtained results from the experimental work have clarified and explained by tables and figures. It has been found that the vibration of evaporative cooler in X, Y and Z-directions increased by using two cylindrical roller bearings than using two of bush bearings. The temperature of cylindrical roller bearings increased When running the evaporative cooler more than bush bearings. the noise of Evaporative Cooler by using both types of Bearings was almost same but with a little Reduce by using cylindrical roller Bearings. Which means the Evaporative Cooler has better Performance by using bush bearings than using cylindrical roller bearings.